Analisis Potensi Eco-Enzyme dari Limbah Kulit Buah dalam Penyisihan dan COD pada Air Sungai Tercemar Secara Batch - Izraini Islamiati Putri; Ansiha Nur (REACTOR: Journal of Research on Chemistry and Engineering, 2026)
River water pollution due to high organic waste load has become a serious environmental issue, marked by high COD values. This study aims to analyze the potential of eco-enzyme from fruit peel waste in reducing COD values in batch-contaminated river water. Eco-enzyme was made from banana, orange, watermelon, papaya, and pineapple peels with a ratio of 3:1:10 (organic material:molasses:water) thru three months of fermentation. Testing was conducted on artificial river water with concentration variations of 5%, 10%, and 15% over 12 days. The parameters measured included pH, temperature, DO, and COD. The results showed that the eco-enzyme has protease, amylase, and lipase bioactivity. The decrease in COD values was intensive from day 1 to day 5 and reached a steady state from day 9 to day 12. A 5% concentration provided the lowest final COD value (22-30 ppm) with banana and pineapple peels as the best raw materials